2014
DOI: 10.1177/1053451214546406
|View full text |Cite
|
Sign up to set email alerts
|

Teacher-, Student-, and Peer-Directed Strategies to Access the General Education Curriculum for Students With Autism

Abstract: Access to the general education curriculum is a critical component of special education today, yet many teachers struggle to implement practices that provide such access. The authors describe how teachers can draw on three levels of supportteacher-, student-, and peer-delivered strategies-to optimize access to the general education curriculum for students with autism. Included are a variety of research-based strategies for facilitating access to the general education curriculum and information on where to find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The use of prompts -instructional techniques designed to trigger desired actions and responses -has been widely adopted in autism studies (MacDuff et al, 2001). Prompts can take various forms, including visual, verbal and modelling prompts (Jones & Zarcone, 2014;Olson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The use of prompts -instructional techniques designed to trigger desired actions and responses -has been widely adopted in autism studies (MacDuff et al, 2001). Prompts can take various forms, including visual, verbal and modelling prompts (Jones & Zarcone, 2014;Olson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding students with ASD, various studies confirm that peer support, as a means of collaboration between students, has positive effects on their academic and social learning (Carter et al, 2017; Olson et al, 2015). This is related to the teacher's knowledge of their pupils and the establishment of trusting relationships, as learners with ASD point out in a study by Hummerstone and Parsons (2021).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding students with ASD, different studies confirm that peer support has positive effects on their academic and social learning (Carter et al ., 2017; Olson et al ., 2015). In this line, McCurdy and Cole (2014) concluded that peer support interventions are effective in reducing the off-task behaviour of students with ASD to a level similar to that of their classroom peers.…”
Section: Introductionmentioning
confidence: 99%